2013
DOI: 10.1002/asi.22818
|View full text |Cite
|
Sign up to set email alerts
|

What happens to computer science research after it is published? Tracking CS research lines

Abstract: Are computer science papers extended after they are published? We have surveyed 200 computer science publications, 100 journal articles, and 100 conference papers, using self‐citations to identify potential and actual continuations. We are interested in determining the proportion of papers that do indeed continue, how and when the continuation takes place, and whether any distinctions are found between the journal and conference populations. Despite the implicit assumption of a research line behind each paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 18 publications
4
32
0
Order By: Relevance
“…In other words, the collaboration in conference articles does not necessarily lead to that in journal publication, or vice versa. Especially if we assume that coauthors from a conference article would work together for developing their article into a journal submission, the mean proportion of overlapping coauthors for conferences (that is, 39.81%) indicate that many conference articles may not be extended into journal articles, possibly supporting the findings of previous studies (Bar‐Ilan, ; Vardi, ; Wainer & Valle, ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In other words, the collaboration in conference articles does not necessarily lead to that in journal publication, or vice versa. Especially if we assume that coauthors from a conference article would work together for developing their article into a journal submission, the mean proportion of overlapping coauthors for conferences (that is, 39.81%) indicate that many conference articles may not be extended into journal articles, possibly supporting the findings of previous studies (Bar‐Ilan, ; Vardi, ; Wainer & Valle, ).…”
Section: Discussionsupporting
confidence: 79%
“…If we assume that a conference article is turned into a journal article with exact or similar title words (for instance, Bar-Ilan, 2010), this observation implies that many CS conference articles may not be extended into journal articles (or vice versa). Previous studies found that the ratios of conference articles that transit into journals have been 25~33% in computer science (Bar-Ilan, 2010; Montesi & Owen, 2008;Wainer & Valle, 2013), which is comparable to the mean ratio of overlapping title words for conferences (26.21%) in this study. A note is that these preceding studies used articles as a unit of analysis, not individual authors.…”
Section: Title Wordssupporting
confidence: 83%
See 1 more Smart Citation
“…According to Wainer, Przibisczki de Oliveira, and Anido (2011), among all articles published by the ACM in 2006, 39% of the references were conference papers and 41% of the references cited more than 10 times were conference papers. Several studies examined differences between conference papers and journal articles: the differences in citations (Freyne et al, 2010;Vrettas & Sanderson, 2015), the patterns of reproducing conference papers for journal publications (Wainer & Valle, 2013), and the patterns of citing references (Wainer et al, 2011). Most studies confirmed the value of conference papers in comparison with journal articles.…”
Section: Comparative Values Of Conference Papersmentioning
confidence: 99%
“…The citation and self-citation rates show CHINZ as roughly comparable to the much larger APCHI conference. Wainer and Valle [19] report approximately half of the computer science papers sampled from the ACM DL from 2003 were uncited in the ACM DL: their conference subset was 44% uncited. The 48% uncited rate for a small regional conference such as CHINZ (Table 3) seems roughly consistent with their results: particularly with the limited audience for CHINZ 2001-3.…”
Section: Assessing Chinzmentioning
confidence: 99%